Dynamic Hypermedia Device, the interactive mode. - Guarnieri, Griselda (Centro de Publicaciones Periódicas Electrónicas de la Universidad Nacional de Rosario, 2012)
The research problem presented in the thesis “Dynamic Hypermedia Device Interactive mode” (DHD)( ) , focuses on the study of the interactions that arise in the complex plot that is set when we are mediatized/mediated in our communication and production by the current possibilities of the Information and Communication Technologies (ICTs). The scope of the problem lies in physical-virtual contexts of teaching and learning at grade and post-grade degree in the form of workshop, thus its relevance to the mention of the word Education.
Received: Dec.2011 Accepted: Mar.2012
Keywords: Higher education; interactivity; interaction; hypermedia; physicovirtual classroom; virtual campus